Analysis of the Impact of Business Capital Assistance on MSME Income in Kabonena Subdistrict - Fiska, Fiska; Tope, Patta; Taqwa, Edhi; Jokolelono, Eko; Jaya, Andi Herman (Transpublika Publisher, 2025)
This research aims to determine the amount of MSME income before and after receiving business capital assistance and to understand the impact of business capital assistance on MSME income in Kabonena Village. The type of research used is quantitative research with a descriptive approach. The sampling technique used is saturated sampling (census), with the sample in this study being 7 MSMEs in food and beverage businesses that are still active and have received BPUM (Productive Assistance for Micro Businesses) stage 1 capital assistance. The data source in this research is primary data. Data collection techniques include observation and interviews using questionnaires as tools. The data analysis tool used is income analysis. The research results show that there are changes in MSME income before and after receiving business capital assistance. The calculation results from income analysis show that the total net income of MSMEs during one month of production before receiving business capital assistance was Rp6,284,600. After receiving business capital assistance, the total net income increased to Rp16,377,800. The research results show that business capital assistance distributed by the government contributes to increasing the income of Micro, Small and Medium Enterprise actors.